Developing a Multidimensional Framework of Learning Technology Adoption in Higher Education: Perspectives from Lecturers and Students - Zulfani Sesmiarni; Emilza Tri Murni; Ridha Ahida (Tarbawi : Jurnal Ilmu Pendidikan, 2026)
This study aims to examine the factors influencing the adoption of learning technologies in higher education and to develop a comprehensive understanding of how individual, institutional, and technological factors interact in supporting successful technology integration. A qualitative descriptive approach was employed. Data were collected through semi-structured, in-depth interviews with lecturers and students at an Indonesian higher education institution. The interview data were analyzed using thematic analysis involving data reduction, coding, categorization, and interpretation to identify recurring patterns and key themes related to technology adoption. The findings reveal seven major factors influencing learning technology adoption: (1) users’ digital competence, (2) institutional support and management policies, (3) perceived ease of use and perceived usefulness, (4) availability of technological infrastructure, (5) quality of digital learning content, (6) technical support services, and (7) individual motivation and learning habits. The results indicate that successful technology adoption is determined not only by technological readiness but also by organizational commitment and users’ adaptive capacities. This study contributes to the literature by proposing a multidimensional perspective that integrates individual, institutional, and technological determinants of learning technology adoption in higher education. The findings have practical implications for policymakers and university leaders in designing sustainable strategies to enhance the implementation of digital learning